Urethro-cutaneous fistula: a rare complication in anti-incontinence surgery with trans-obturator tapes sling - Treviño Cavazos, Omar; Guerrero Reyes, Guadalupe; Gutiérrez González , Adrián; Hernández Velázquez, Ricardo; Loya Maldonado , Karen M.; Leyva Vázquez , José I.; Reyes Alcaraz , Jennifer E.; Robledo Torres , Alejandra; Saca Cuevas, Sara Y.; Herrera Morales, Juan C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
This case report presents a rare complication of tension-free mid-urethral tape surgery by the obturator approach (TOT) in the form of a urethro-cutaneous fistula. The patient underwent successful surgical repair, highlighting the importance of intraoperative cystoscopy to minimize surgical risks and complications. Tension-free mid-urethral tape surgery is a commonly performed procedure for the treatment of stress urinary incontinence (SUI). However, complications can occur, albeit rarely. In this case, a 52-year-old female patient developed a urethro-cutaneous fistula following TOT surgery. The fistula was identified by the presence of urine leakage at the right inguinal level, leading to significant distress and discomfort for the patient. Prompt diagnosis and appropriate management are crucial in such cases. The patient underwent surgical repair, which involved excision of the fistulous tract. The procedure was successful, resulting in complete resolution of the fistula and restoration of normal urinary function. In conclusion, this case report highlights the occurrence of a rare complication, namely a urethro-cutaneous fistula, following TOT surgery. The successful surgical repair emphasizes the importance of prompt diagnosis and appropriate management. Furthermore, the authors propose that an intraoperative cystoscopic evaluation be considered, even after a TOT procedure. Especially in cases that present risk factors or in hospital-school institutions. By implementing this practice, surgeons can enhance patient safety and improve surgical outcomes in anti-incontinence procedures.